Life-Saving Treatments for Spinal Muscular Atrophy: Global Access and Availability - Armengol, Victor D.; Darras, Basil T.; Abulaban, Ahmad A.; Alshehri, Ali; Barisic, Nina; Ben-Omran, Tawfeg; Bernert, Guenther; Castiglioni, Claudia; Chien, Yin-Hsiu; Farrar, Michelle A.; Kandawasvika, Gwendoline; Khadilkar, Satish; et al. (Neurology. Clinical practice, 2024)
Spinal muscular atrophy (SMA) is a neurodegenerative disorder manifesting with progressive muscle weakness and atrophy. SMA type 1 used to be fatal within the first 2 years of life, but is now treatable with therapies targeting splicing modification and gene replacement. Nusinersen, risdiplam, and onasemnogene abeparvovec-xioi improve survival, motor strength, endurance, and ability to thrive, allowing many patients to potentially attain a normal life; all have been recently approved by major regulatory agencies. Although these therapies have revolutionized the world of SMA, they are associated with a high economic burden, and access to these therapies is limited in some countries. The primary objective of this study was to compare the availability and implementation of treatment of SMA from different regions of the world. In this qualitative study, we surveyed health care providers from 21 countries regarding their experiences caring for patients with SMA. The main outcome measures were provider survey responses on newborn screening, drug availability/access, barriers to treatment, and related questions. Twenty-four providers from 21 countries with decades of experience (mean 26 years) in treating patients with SMA responded to the survey. Nusinersen was the most available therapy for SMA. Our survey showed that while genetic testing is usually available, newborn screening is still unavailable in many countries. The provider-reported treatment cost also varied between countries, and economic burden was a major barrier in treating patients with SMA. Overall, this survey highlights the global inequality in managing patients with SMA. The spread of newborn screening is essential in ensuring improved access to care for patients with SMA. With the advancement of neurotherapeutics, more genetic diseases will soon be treatable, and addressing the global inequality in clinical care will require novel approaches to mitigate such inequality in the future.